2020
DOI: 10.1111/fcp.12590
|View full text |Cite
|
Sign up to set email alerts
|

Sumatriptan reduces severity of status epilepticus induced by lithium–pilocarpine through nitrergic transmission and 5‐HT1B/D receptors in rats: A pharmacological‐based evidence

Abstract: Status epilepticus (SE) is a life‐threatening neurologic disorder that can be as both cause and consequence of neuroinflammation. In addition to previous reports on anti‐inflammatory property of the anti‐migraine medication sumatriptan, we have recently shown its anticonvulsive effects on pentylenetetrazole‐induced seizure in mice. In the present study, we investigated further (i) the effects of sumatriptan in the lithium–pilocarpine SE model in rats, and (ii) the possible involvement of nitric oxide (NO), 5‐h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 57 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Eslami et al found that sumatriptan (0.001–1 mg/kg) improved status epilepticus score by reducing TNF‐α and NO in rat's brain. Further, selective 5HT1B/D antagonist significantly reverted this changes (Eslami et al, 2020).…”
Section: Resultsmentioning
confidence: 97%
“…Eslami et al found that sumatriptan (0.001–1 mg/kg) improved status epilepticus score by reducing TNF‐α and NO in rat's brain. Further, selective 5HT1B/D antagonist significantly reverted this changes (Eslami et al, 2020).…”
Section: Resultsmentioning
confidence: 97%
“…The absorbance was determined at 540 nm after 15 min using an automated plate reader. The final concentrations were adjusted for the protein concentration of the samples, and the final results were stated as nmol/mg-protein [ 2 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The chemical dosage, route of injection, and administration time were found based on our previous hypothesis, pharmacokinetic consideration, and pilot studies. 8 , 23 …”
Section: Methodsmentioning
confidence: 99%